Analisis Implementasi Pemenuhan Hak-Hak Korban Tindak Pidana Terorisme Berdasarkan Undang-Undang Nomor 5 Tahun 2018 : (Studi Kasus Bom Bali 1 dan 2) - Desti Sarah; Syifa Zalfa Swargana; Bagas Rifqi Gunawan; Gunawan Aditya Pratama; Jelita Ayu Faradilla; Fadila Azahra; Savina Zulhijjah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The act of terrorism is barbaric because it puts many people in danger. Indonesia has unfortunately experienced terrorism multiple times, including the Bali bombings in 2002 and 2005, known as Bali I and Bali II. These attacks resulted in numerous casualties. The government's response to terrorism should not just focus on catching the perpetrators, but also on ensuring the well-being of the victims. This includes providing compensation and ensuring their rights are protected under the law. The government's primary responsibility is to guarantee the safety of its citizens and uphold the rights of victims. This article aims to investigate whether the Indonesian government has adequately fulfilled the rights of the victims of the Bali bombings. The research will use a normative legal research method, combining legal analysis with a case study approach. Secondary data will be used to support the findings. Ultimately, the research will identify any gaps between existing laws and the reality faced by victims of terrorism in Indonesia.